IMPROVING THERMAL AND ENERGY PERFORMANCE OF RESIDENTIAL BUILDINGS IN NIGERIA BY DEVELOPING AND USING ECO-FRIENDLY AND SUSTAINABLE LOCAL MATERIALS. - Shem Lekjep, Ripnung; Joanna Kagai, Kaliat; David Chong, Jonathan; Andrew Baji, Julius (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
The effort to consume more energy inside buildings is driven by the extraordinarily high temperatures and intense sunlight which is a problem in most developing countries, especially those in tropical climates like Nigeria. This study investigates how locally produced, environmentally friendly materials enhance the energy and thermal efficiency of residential structures in Nigeria. The study adopted a literature approach, and the outcome shows that sustainable local materials such as wood, bamboo, straw bales, earth, clay brick, stone, timber, and laterite have the advantage of accessibility, biodegradability, energy effectiveness, reusability, thermal comfort, and ozone friendliness, as such the use of these materials develops and optimise the thermal and energy performance of residences. As a result, residential structures may use resources more efficiently, have less impact on the environment, and perform better; economically, environmentally, and socially. The study recommended that that residential buildings need to continually adapt to technology breakthroughs, and regulatory and legal requirements to meet the dynamics of the built environment to develop and improve thermal and energy performance and sustainability in buildings.